Academic Self-Efficacy as A Mediator on The Relationship Between Academic Motivation and Academic Achievement of College Students During the Online Learning Period - Vivik Shofiah; Rexsy Taruna; Yulita Kurniawaty Asra; Khairunnas Rajab; Che Zarrina Sa’ari (Universitas Muhammadiyah Yogyakarta, 2023)
There are limitations to the review of the role of academic self-efficacy as a mediator of the link between academic motivation and academic achievement in students. This study aims to determine the direct, indirect, and total effects of academic self-efficacy as a mediating relationship between academic motivation and achievement. This study used 127 college students and health workers as samples. The profile of academic motivation was measured using the academic motivation scale, and academic self-efficacy was measured using the learning self-efficacy scale. The analysis technique in this study used the Robust Bootstrap Test for Mediation Analysis. This study explained that academic self-efficacy empirically played a role in mediating the relationship between academic motivation and academic achievement (β = .26; p .001; CI: [0.198-0.330]).